2022
DOI: 10.1109/tbme.2021.3085170
|View full text |Cite
|
Sign up to set email alerts
|

Effective Ultrasonic Stimulation in Human Peripheral Nervous System

Abstract: Low-intensity ultrasound can stimulate excitable cells in a noninvasive and targeted manner, but which parameters are effective has remained elusive. This question has been difficult to answer because differences in transducers and parameters-frequency in particular-lead to profound differences in the stimulated tissue volumes. The objective of this study is to control for these differences and evaluate which ultrasound parameters are effective in stimulating excitable cells. Methods: Here, we stimulated the h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 75 publications
(79 reference statements)
0
25
0
Order By: Relevance
“…Here, ultrasound stimulation with pulse repetition frequency of ~ 300 kHz was selected due to its higher efficacy in human and animal brain neuromodulation compared with other higher frequencies. Previous studies [ 32 , 33 ] have shown that neuromodulation in vivo is more effective at frequencies less than 1 MHz, especially 300 kHz, than at 1 MHz. In addition, here the tUS stimulation pulsed at 40 Hz resulted in a strong response, similar to the auditory steady-state response to the click sounds at 40 Hz [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, ultrasound stimulation with pulse repetition frequency of ~ 300 kHz was selected due to its higher efficacy in human and animal brain neuromodulation compared with other higher frequencies. Previous studies [ 32 , 33 ] have shown that neuromodulation in vivo is more effective at frequencies less than 1 MHz, especially 300 kHz, than at 1 MHz. In addition, here the tUS stimulation pulsed at 40 Hz resulted in a strong response, similar to the auditory steady-state response to the click sounds at 40 Hz [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound has been reported to both suppress and augment electrically evoked activity in the mammalian and invertebrate PNS ( 14 20 ). Notably, human psychophysical studies revealed that transdermal sonication induced somatic sensations such as touch, thermoreception, and pain, suggesting that ultrasound activates sensory neurons ( 15 , 21 23 ). In addition, noninvasive sonication of the mouse sciatic nerve elicited muscle activity, indicating that FUS excites motor neurons ( 24 , 25 ).…”
mentioning
confidence: 99%
“…The successful stimulation of nerves following the RTT compensation provides a physiologically-relevant validation of the method and thus serves as a proof of concept. Notably, however, the stimulation of peripheral nerves differs significantly from stimulation of neurons in the brain 60 . Therefore, these findings should be interpreted as a physiological readout of the compensated intensity rather than a direct evidence of stimulation of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of RTT and the associated hardware to stimulate nerves at depth is therefore critical for effective future treatments. Ultrasonic stimulation of neurons generally requires lower ultrasound intensities than stimulation of nerves 5,52,62 . Moreover, ultrasonic stimulation of nerves in the brain also appears to require lower stimulation intensities compared to nerves in the periphery 62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation